2020
DOI: 10.1042/bsr20194118
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-mediated pyroptosis in human hepatoma-derived HuH-7 cells induced by a branched-chain polyunsaturated fatty acid, geranylgeranoic acid

Abstract: A branched-chain polyunsaturated fatty acid, geranylgeranoic acid (GGA; C20:4), which is an endogenous metabolite derived from the mevalonate pathway in mammals, has been reported to induce cell death in human hepatoma cells. We have previously shown that the lipid-induced unfolded protein response (UPR) is an upstream cellular process for an incomplete autophagic response that might be involved in GGA-induced cell death. Here, we found that Toll-like receptor 4 (TLR4)-mediated pyroptosis in HuH-7 cells occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(79 citation statements)
references
References 75 publications
0
79
0
Order By: Relevance
“…In fact, GGA is a branched‐chain polyunsaturated fatty acid, an endogenous metabolite derived from the mevalonate pathway in mammals. 212 …”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, GGA is a branched‐chain polyunsaturated fatty acid, an endogenous metabolite derived from the mevalonate pathway in mammals. 212 …”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…It has been reported that geranylgeranoic acid (GGA) (C20:4) could induce pyroptotic cell death in human hepatoma‐derived HuH‐7 via toll‐like receptor 4 (TLR4) signaling pathway. In fact, GGA is a branched‐chain polyunsaturated fatty acid, an endogenous metabolite derived from the mevalonate pathway in mammals 212 …”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…In these studies, GGA was reported to induce cell death in human hepatoma cells via endoplasmic reticulum stress response and incomplete autophagic response [ 7 , 8 ]. Most recently, we reported that GGA induces Toll-like receptor 4 (TLR4)-mediated pyroptosis in human hepatoma-derived cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that GGA induces cell death in human hepatoma cells via the unfolded protein response (UPR ER ) and an incomplete response of autophagy [ 10 , 11 ]. Most recently, we concluded that GGA induces Toll-like receptor 4 (TLR4)-signaled pyroptosis in human hepatoma cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…GGA causes activation of caspase-4 via TLR4-mediated UPR ER , resulting in cleavage of gasdermin D (GSDMD) and the translocation of its N-terminal fragment to the plasma membrane leading to the formation of the GSDMD pore [ 12 ]. Another TLR4 signaling causes increased reactive oxygen species production in the mitochondria, leading to the transfer of NF-κB to the nucleus and priming the NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%